3D Printing: Fabrication of Thermally Stable Silver–Organic Complex (TS‐SOC) Based Conductible Filament Materials for 3D Printing (Adv. Mater. Technol. 9/2017). Issue 9 (14th September 2017) - Kim, Tae Yun; Kim, Sang Il; Park, Jong‐Jin
Abstract : In article number1700079, Jong‐Jin Park and co‐workers report thermally stable and electrical conductive filaments for 3D printing. Minimizing the contents of conductive fillers is achieved by forming silver‐organic complex (SOC). Also, the construction of cage structure makes the filament more durable even at high temperature like under extrusion and 3D printing. It is the first demonstration of thermally stable (TS)‐SOC based filaments mechanism and manufacturing process. It reveals the potential to develop the conductive 3D printing for easy customizing the parts in the electronics manufacturing industry.